Bismarck's first war : the campaign of Schleswig and Jutland 1864 - Embree, Michael (Helion, 2006)
This book chronicles the final conflict over the now almost forgotten "Schleswig-Holstein Question", once a pivotal issue for the great powers of Europe. The campaign of Schleswig and Jutland was also the first of Otto von Bismarck's Wars of German Unification, which together created a united German Empire under Prussian leadership. The detailed story of this, the last of the "Cabinet Wars", is told here for the first time in English, compiled from numerous published and unpublished sources, including many contemporary and first hand accounts, as well as official reports. This is an invaluable.